2017
DOI: 10.1099/ijsem.0.002416
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosopumilus maritimus gen. nov., sp. nov., Nitrosopumilus cobalaminigenes sp. nov., Nitrosopumilus oxyclinae sp. nov., and Nitrosopumilus ureiphilus sp. nov., four marine ammonia-oxidizing archaea of the phylum Thaumarchaeota

Abstract: Nitrosopumilus maritimus gen. nov., sp. nov., Nitrosopumilus cobalaminigenes sp. nov., Nitrosopumilus oxyclinae sp. nov., and Nitrosopumilus ureiphilus sp. nov., four marine ammonia-oxidizing archaea of the phylum Thaumarchaeota

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
119
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(131 citation statements)
references
References 81 publications
9
119
0
3
Order By: Relevance
“…Sediment samples collected from the SCTLD epidemic zone had significantly higher relative abundances of the family Nitrosopumilaceae compared to both endemic and vulnerable zones (Figure 3C). Nitrosopumilaceae consist of a group of ammonia-oxidizing archaea (Qin et al, 2017) commonly found in marine environments (Gajigan et al, 2018;He et al, 2018) and are positively correlated with high levels of nitrite and nitrate (Gajigan et al, 2018). Nitrosopumilaceae is likely not directly responsible for SCTLD, but this group of archaea may signify environmental conditions that promote the prevalence of SCTLD, or could be a secondary response to disease occurrence in the reef.…”
Section: Potential Microbial Signatures Associated With Sctld Outbreamentioning
confidence: 99%
“…Sediment samples collected from the SCTLD epidemic zone had significantly higher relative abundances of the family Nitrosopumilaceae compared to both endemic and vulnerable zones (Figure 3C). Nitrosopumilaceae consist of a group of ammonia-oxidizing archaea (Qin et al, 2017) commonly found in marine environments (Gajigan et al, 2018;He et al, 2018) and are positively correlated with high levels of nitrite and nitrate (Gajigan et al, 2018). Nitrosopumilaceae is likely not directly responsible for SCTLD, but this group of archaea may signify environmental conditions that promote the prevalence of SCTLD, or could be a secondary response to disease occurrence in the reef.…”
Section: Potential Microbial Signatures Associated With Sctld Outbreamentioning
confidence: 99%
“…Relatively little is known about the biogeochemical cycling of DON compared to that of dissolved inorganic nitrogen (predominately ammonium, nitrite, and nitrate). Recent reports show that some cultivated Thaumarchaeota can grow by oxidizing the N in urea (Tourna et al ; Bayer et al ; Qin et al ; Carini et al ) or cyanate (Palatinszky et al ), that Thaumarchaeota in the coastal Arctic Ocean can assimilate significant amounts of urea‐N into DNA (Connelly et al ), and that thaumarchaeal ureC genes are present in many ocean basins (Yakimov et al ; Alonso‐Sáez et al ; Smith et al ; Tolar et al ). These observations suggest that some organic N compounds can be oxidized by nitrifiers, verified by recent measurements of the contribution of urea‐derived N to nitrification in several Thaumarchaeota‐dominated nitrifier communities (Tolar et al ).…”
mentioning
confidence: 99%
“…Pairwise relative phylogenetic distances between each genome were subjected to hierarchical clustering using single linkage Pearson correlation and taxonomic levels corresponding to class, order and family were defined as Pearson’s distances of less than 0.34, 0.13 and 0.015, respectively. These cut-off distances were chosen by comparison to existing thaumarchaeotal taxonomy 5-7, 55-63 . The taxonomic levels for genus and species levels were defined with AAI thresholds higher than 70% and 95%, respectively 64, 65 .…”
Section: Methodsmentioning
confidence: 99%
“…Ammonia oxidation is limited to a small number of microbial phyla but is one of the most important microbial metabolisms on the planet as it implements an essential and rate-limiting step in the nitrogen cycle, the conversion of ammonia to nitrite (via hydroxylamine). Within Thaumarchaeota, ammonia oxidising archaea (AOA) are ubiquitous and abundant in mesophilic soils and oceans, and are classically placed in four order-level phylogenetic lineages 1 : the Nitrososphaerales 4 , Nitrosopumilales 5 , Candidatus Nitrosotaleales 6 and Candidatus Nitrosocaldales 7 .…”
Section: Introductionmentioning
confidence: 99%